Pollution indices of brackish water and sediments of major mangrove sites along Arabian Sea coast of Pakistan - Malik Wajid Hussain Chan; Muhammad Ibrahim; Muhammad Qasim; Manzer. H. Siddiqui; Saud Alamri; Pirzada Jamal Ahmed Siddiqui; Salman Gulzar; Muhammad Azeem; Troy T. Handlovic; M. Farooq Wahab; Alanoud T. Alfagham; Munawwer Rasheed (Scientific Reports)
Abstract Heavy metal (HM) contamination poses a significant environmental threat to Mangrove ecosystems, particularly in industrial and urban-influenced regions. This study has investigated the spatial and seasonal distribution of HM in water and sediment samples from three major mangrove sites along the Arabian Sea coast of Pakistan, Indus Delta, Sandspit and Miani Hor. Ten heavy metals (HM)- aluminum (Al), arsenic (Ar), cadmium (Cd), chromium (Cr), copper (Cu), iron (Fe), lead (Pb), mercury (Hg), selenium (Se), and zinc (Zn) were assessed using multiple pollution indices to evaluate the contamination levels and ecological risks. Multivariate analysis (MANOVA) and principal component analysis (PCA) revealed significant effects of sample types (water and sediments), sites, and seasons on HM concentrations. Sandspit exhibited the highest pollution level primarily due to industrial discharge and wastewater influx. Pollution indices identified Sandspit as the most contaminated mangrove stand. In seawater, HM Contamination factor (Cf) followed the order: Hg > Cr > Al > Pb > As > Cd > Fe > Cu > Zn > Se, whereas individual Heavy Metal Pollution Index (HPI) sequence was Hg > Cd > Al > Pb > Cr > As > Cu > Fe > Se > Zn. Seasonal variations, especially during the monsoon, intensified HM mobilization, further deteriorating water quality. The excessive Hg levels surpass national and international safety limits, posing ecological and public health risks. The prolonged retention of Cd, Cu, and Al in sediments indicates persistent contamination affecting mangrove vegetation and associated marine biodiversity. Urgent intervention is required to regulate industrial waste, improve pollution control, and implement sustainable remediation strategies to protect coastal ecosystems.